Fish in the diet: A review. Issue 2 (15th May 2013) - Weichselbaum, E.; Coe, S.; Buttriss, J.; Stanner, S.
Summary Fish plays a useful role in a healthy and balanced diet, and its consumption has long been associated with several health benefits. Fish provides a variety of nutrients, including protein and long‐chain omega‐3 polyunsaturated fatty acids (n‐3 PUFAs), as well as micronutrients including selenium, iodine, potassium, vitamin D and B‐vitamins. Intakes of some of these micronutrients, including iodine and vitamin D, are low in some population groups in the UK, which makes fish a valuable contributor to intakes of these. The long‐chain n‐3 PUFA eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), present in oil‐rich fish and fish oil, have been suggested to be associated with beneficial health outcomes. In this paper, we review the evidence associating fish and long‐chain n‐3 PUFAs with various health outcomes. Evidence from observational studies shows a protective effect of fish intake on risk of cardiovascular disease (CVD; including stroke). Eating at least two portions of fish per week has been associated with a 23–25% lower risk of death from coronary heart disease (CHD) compared with those eating no or very little fish; eating fish once a week has been associated with a 15% lower risk of CHD death. Fish intake seems only moderately associated with lower risk of stroke, with results from meta‐analyses showing a risk reduction of between 6% and 18% in those eating fish 2–4 times per week compared with those eating none. There have been some inconsistencies in study findings relating to fish intake and risk of CVD. Differences in habitual fish intakes of the study populations may account for some of this inconsistency. Evidence from randomised controlled trials (RCTs) on the effect of long‐chain n‐3 PUFA supplementation on CVD risk has come mainly from secondary prevention studies and is inconsistent. While early studies support a protective effect, recent studies do not support the hypothesis that long‐chain n‐3 PUFA supplementation is beneficial in secondary prevention of CVD. Different study outcomes have been influenced by variations in study design and the characteristics of the study populations. Furthermore, the increased use of modern treatments for cardiovascular risk factors (e.g. statins) may not have been sufficiently controlled for in more recent studies. Treatment doses of long‐chain n‐3 PUFA also varied substantially between studies, ranging from 0.3 to 6.9 g/day. Current evidence suggests that there is no association between fish consumption and risk of type 2 diabetes. We also found no evidence to suggest that fish intake has a protective effect on several types of cancer (pancreas, prostate, bladder, stomach and ovaries). However, studies do suggest that maternal fish intake during pregnancy may reduce the risk of eczema and asthma in her baby, the evidence being somewhat more consistent for eczema. There may also be a link between fish intake during infancy and childhood and the risk of developing asthma and eczema later in childhood, although the evidence is inconsistent and more studies are needed to clarify the situation. The long‐chain fatty acid DHA is crucial for development of the brain and the central nervous system in early life. While studies suggest that fish intake in early life contributes to cognitive development, supplementation with EPA and DHA does not seem to have a beneficial effect on cognitive function in childhood. The European Food Safety Authority (EFSA) suggests that pregnant and breastfeeding women increase their intake of preformed DHA by 100–200 g/day in addition to the suggested average intake level of long‐chain n‐3 PUFA for adults (250 mg EPA + DHA combined). EFSA proposes that an intake of 1–2 portions of oil‐rich fish per week should be compatible with an adequate DHA supply during pregnancy and lactation. There is some evidence to suggest that higher fish intake, dietary DHA intake and DHA levels in the blood among older adults may be positively associated with a lower risk of dementia and Alzheimer's disease (AD). In some prospective studies, risk of AD and dementia in those having the highest fish intake, or the highest blood DHA levels, was about half that of those who ate a little or no fish or had a low blood DHA level. In one prospective study, eating fish once a week was associated with a 60% lower risk of AD compared with those who rarely or never ate fish. However, some studies have found no association, and more evidence will be needed to draw reliable conclusions. Fish intake may be associated with slower cognitive decline, but the evidence is very limited and more studies are needed. Data from RCTs do not suggest that long‐chain n‐3 PUFA supplements are effective in preventing cognitive decline. There is some evidence from cohort and cross‐sectional studies that fish intake may be associated with better bone health, but not all studies have found such an association. Oil‐rich fish, in particular, is an important dietary source of vitamin D, which is important for bone health, and fish consumed with soft bones are a good source of calcium, which is the most abundant mineral in the skeleton. When making recommendations on fish intake, consideration has to be given to the sustainability of fish supplies. Much work has been done already to ensure that fish stocks are not depleted and more efforts will be required to ensure supplies of fish for future generations. Overall, it is evident that including fish in the diet is associated with several health benefits. The extent to which long‐chain n‐3 PUFA per se contributes to these various effects has yet to be established. It is likely that other components in fish, such as selenium, potassium, vitamin D or B‐vitamins, and other dietary aspects (i.e. foods typically eaten with fish or foods displaced by fish) contribute to the positive health effects.